A simplicidade mordente de um protagonista-escritor outsider: estudo de Ask the Dust e Dreams from Bunker Hill de John fante - Abelin, Bruna Arozi (2015)
In Ask the Dust (1939) and Dreams from Bunker Hill (1983), John Fante (1909-1983) represents the obliterated side of American life during the Great Depression by making use of an apparently simple narrative style. Besides focusing on the importance of the marginal side of the United States in the 1930s, Fante presents young Arturo Bandini as the protagonist who survives in Los Angeles during the economic crisis and aims at becoming a great writer that contends for space in the cultural market of the metropolis of entertainment. Through obscene vocabulary and scenes, Fante represents the most negative aspects experienced by those who live in a metropolis, such as isolation, solitude, vice, and madness. Therefore, Fante s fiction has thematic and formal aspects that allow us to establish relations with the New Realism, a movement of the Arts in the first half of the twentieth century, which also crudely explored the negative aspects of life in the United States. Thus, this study discusses the potential meaningfulness of thematic and aesthetic aspects of Ask the Dust and Dreams from Bunker Hill, two novels that present the relation established by the writer, who is an outsider, with the city, the people, and the craft of writing in modern times.